Aptitude treatment interaction of cognitive learning styles and ESL methodologies - Mina, John Rivera (2007)
This research aimed to establish the effects of cognitive learning styles and English as a Second Language (ESL) teaching methodologies in students' achievement in English based on their pre and posttest scores. Prior to treatment periods, the Group Embedded Figures Tests was administered to the subjects of the study to determine their degree of field dependence or their cognitive learning styles. The inductive and deductive methods of ESL were used in teaching the students. The data revealed that there was a significant positive relationship between cognitive learning style and ESL teaching methodologies. The mean gain scores of the field independent learners in the inductive lessons were significantly higher than the mean gain scores of the field dependent learners. Both groups excelled in the deductive lessons.